1999
DOI: 10.4269/ajtmh.1999.60.350
|View full text |Cite
|
Sign up to set email alerts
|

Testing the efficacy of a recombinant merozoite surface protein (MSP-1(19) of Plasmodium vivax in Saimiri boliviensis monkeys.

Abstract: Abstract. Saimiri boliviensis monkeys were immunized with the yeast-expressed recombinant protein yP 2 P 30 Pv200 19 . The antigen consisted of the C-terminus (amino acid Asn 1622 -Ser 1729 ) of the merozoite surface protein 1 of the Plasmodium vivax Salvador I strain. Two universal T helper cell epitopes (P 2 and P 30 ) of tetanus toxin and six histidine residues for purification purposes were attached to the N-and C-termini, respectively. Four groups of five monkeys were given three immunizations at four-wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 29 publications
1
22
0
1
Order By: Relevance
“…The results of this study clearly indicate the ability of MSP-1 42 with Montanide ISA720 to induce a partially protective immune response in primates using an adjuvant acceptable for human use instead of FCA. Similar partial protection has been reported in two other challenge trials using PvMSP-1 19 and a nonionic block copolymer in the splenetomized Saimiri monkey model against P. vivax challenge (45,11).…”
Section: Discussionsupporting
confidence: 83%
“…The results of this study clearly indicate the ability of MSP-1 42 with Montanide ISA720 to induce a partially protective immune response in primates using an adjuvant acceptable for human use instead of FCA. Similar partial protection has been reported in two other challenge trials using PvMSP-1 19 and a nonionic block copolymer in the splenetomized Saimiri monkey model against P. vivax challenge (45,11).…”
Section: Discussionsupporting
confidence: 83%
“…4 Because antibodies specific to this protein, particularly to the C-terminal region (42-kD and 19-kD subfragments), have been shown to block parasite invasion in vitro [5][6][7] and to induce protective immunity in animal models, [8][9][10][11][12][13] this MSP-1 fragment has long been considered a major vaccine candidate. 12,14,15 Limited effort has been invested in the definition and testing of other MSP-1 fragments as potential vaccine candidates.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown in rodent models of malaria that the presence of the two epidermal growth factorlike domains in the p19 region is critical for the induction of MSP-1-based protective immunity (19,20). In addition, it has been shown that immunization with recombinant P. vivax MSP-1 p19 made in baculovirus-infected insect cells can protect monkeys against parasite challenge (6,30). Although the p33 region has not been shown to be critical for protection, several immunodominant B-and T-cell epitopes have been mapped to it; these epitopes are highly immunogenic during natural malaria infection in humans (10).…”
mentioning
confidence: 99%